1996
DOI: 10.1007/bf02803765
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between pancreatic endocrine and exocrine function and characteristics of pancreatic endocrine function in patients with diabetes mellitus owing to chronic pancreatitis

Abstract: The urinary CPR excretion in controls was 94.9 +/- 20.5 micrograms/d. The urinary CPR excretion in calcific pancreatitis was 12.8 +/- 7.4 micrograms/d and it resembled that in IDDM (9.4 +/- 5.8 micrograms/d). The urinary CPR excretion in noncalcific pancreatitis was 41.5 +/- 30.1 micrograms/d, being similar to that in NIDDM (49.3 +/- 21.0 micrograms/d). The plasma glucagon level in calcific pancreatitis was 64.1 +/- 15.9 rho g/mL, which was significantly lower than the values in IDDM (111.2 +/- 50.2 rho g/mL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
0
15
0
4
Order By: Relevance
“…Loss and impairment of beta cell function and loss of alpha cell function have been proposed as possible main mechanisms of the decreased insulin production, along with concurrent hepatic disease and malnutrition [25]. In advanced stages of CP, the residual capacities of acinar cells and ductal cells are correlated with endocrine capacities, as indicated by urinary C peptide excretion and plasma glucagon levels [27]. In animal models of CP, the islets show mononuclear infiltration, peri- and intrainsular fibrosis, endothelial vascular damage, insulin- and glucagon-producing cell alterations, and reduced insulin immunoreactivity [28].…”
Section: Discussionmentioning
confidence: 99%
“…Loss and impairment of beta cell function and loss of alpha cell function have been proposed as possible main mechanisms of the decreased insulin production, along with concurrent hepatic disease and malnutrition [25]. In advanced stages of CP, the residual capacities of acinar cells and ductal cells are correlated with endocrine capacities, as indicated by urinary C peptide excretion and plasma glucagon levels [27]. In animal models of CP, the islets show mononuclear infiltration, peri- and intrainsular fibrosis, endothelial vascular damage, insulin- and glucagon-producing cell alterations, and reduced insulin immunoreactivity [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that basal levels of glucagon are maintained in patients with CP, although the stimulated response is lowered [36,37] . A recent study in 33 patients with CP and no obvious signs of cirrhosis reported that even basal glucagon secretion was signifi cantly lowered in patients with overt diabetes, compared to patients with primary diabetes (insulin-dependent and non-dependent diabetes mellitus) and healthy controls [38] . However, in a small study of 10 patients with CP -examined with an arginine test -the authors reported that the pancreatic glucagon showed a brisk early increase greater than that seen in normal subjects [39] .…”
Section: Endocrine Function In Cpmentioning
confidence: 99%
“…It has been reported that both insulin and glucagon secretion are disturbed more strongly in calcifi c than in noncalcifi c pancreatitis [38] . The incidence of overt diabetes was 30% in noncalcifi c CP, as compared to 70% in calcifi c pancreatitis [32] .…”
Section: Pancreatic Diabetesmentioning
confidence: 99%
“…There were also numerous reports on changes of the macroscopic morphology and histology of the exocrine pancreas in these patients [5][6][7][8][9], including reports on pancreatic duct changes resembling chronic pancreatitis [10,11]. Several hypotheses have been raised to explain these findings, including exocrine diseases as a cause of endocrine dysfunction [12][13][14][15], exocrine failure as a diabetic complication [16][17][18][19][20][21][22] or a pathological process affecting the complete organ [23][24][25]. In a recent study we used an indirect test of exocrine function -fecal elastase 1 concentration (FEC) measurement -to investigate type 1 and type 2 diabetics in a larger study population [26].…”
Section: Introductionmentioning
confidence: 99%